"The War, like the Wicked Wand of a Wizard, Strikes Me and Carry Away All that I Have Loved:" Soldiers' Family Lives and Petition Writing in Ijebu, Southwestern Nigeria, 1943–1945. (21st February 2018) - Coates, Oliver
Abstract: The social isolation of the African soldiery is a recurrent assumption in the historiography of the Second World War in Anglophone Africa; such factors as the experience of Hausa soldiers within a cohesive barracks community, a strong sense of warrior identity, and few ties to civilian life are too often generalized into an account of the soldiery as necessarily isolated. Focusing on Ijebu in southwestern Nigeria, an area with little history of colonial military service prior to the Second World War, this paper will argue that far from being deeply isolated, Ijebu soldiers and their families strove desperately to maintain customary obligations during the men's military service in South Asia and the Middle East in 1944 and 1945. By examining soldiers' petitions to the Ijebu District Officer, as well as petitions from their wives, brothers, and parents, we will see that soldiers were bound by a powerful sense of obligation to their extended family not only in terms of financial support, but also in relation to labor, security, administration, and redistribution. Contextualizing these sources in terms of the ethnography of customary obligations in southwestern Nigeria, this paper will argue that neither soldiers nor their families primarily regarded these men as martial professionals, but instead perceived soldiering as a subordinate and secondary concern to family and economic commitments, as expressed through customary obligations. Although it likely differs from the experience of soldiers from supposedly "martial" groups, the experience of the Ijebu sheds light on the military service of the newer groups recruited during the war. Résumé: L'isolement social des soldats africains est une hypothèse récurrente dans l'historiographie de la Seconde Guerre mondiale en Afrique anglophone; des facteurs tels que l'expérience des soldats haoussas dans une communauté cohésive des casernes, un fort sentiment d'identité guerrière, et peu de liens avec la vie civile sont trop souvent généralisés dans un récit qui tend à prendre pour acquis un isolement des soldats. En se concentrant sur Ijebu dans le sud-ouest du Nigeria, une région avec peu d'histoire du service militaire colonial avant la Seconde Guerre mondiale, cet article suggère que loin d'être profondément isolés, les soldats d'Ijebu et leurs familles s'efforcent désespérément de maintenir leurs obligations coutumières pendant le service militaire masculin. En examinant les pétitions des soldats auprès de l'officier du district d'Ijebu, ainsi que les pétitions de leurs épouses, de leurs frères et de leurs parents, nous verrons que les soldats étaient liés par un sentiment puissant d'obligation envers leur famille élargie non seulement en termes de soutien financier, mais aussi pour le travail, la sécurité, l'administration et la redistribution. Contextualisant ces sources en termes d'ethnographie des obligations coutumières dans le sud-ouest du Nigeria, cet article soutient que ni les soldats ni leurs familles ne considéraient ces hommes comme des professionnels de la guerre, mais considéraient leur présence dans l'armée comme une préoccupation subordonnée et secondaire aux engagements familiaux et économiques exprimés par des obligations coutumières. Bien que cela diffère probablement de l'expérience des soldats de groupes supposés "martiaux, " l'expérience d'Ijebu met en lumière le service militaire des groupes recrutés plus tardivement pendant la guerre.